Our experience of treatment of purulent arthritis in lower extremities after burn injury - B.M. Shakirov; D.Sh. Karabaev; S.X. Zoxidova; Sh. Ziyadullaev (Burns Open)
Background: The burn wound is directly affected by the general condition of the patient and also has a direct impact on the same leading to conditions pathology of the musculoskeletal system. Purulent arthritis is a pathological condition in which the joints of the body get inflamed as a result of bacterial infection.The aim of the present study was identification of purulent arthritis patients and to evaluate different surgical treatment in burn patients’ low extremities. Material and methods: During a 11-year period, 39 patients with burn injuries complicated by purulent arthritis of the joints of the lower extremities treated in the burn department of the Samarkand Center of Emergency Medical Care, Samarkand, Uzbekistan between 2010 and 2020 were enrolled in the present study. The diagnosis is made on the basis of a characteristic anamnesis. Blood tests confirming the presence of acute inflammation. The main diagnostic method purulent arthritis is puncture of the joint with subsequent examination of the punctate. All patients received comprehensive general and local treatment included necrotomy, necrectomy and 1 to 3 operations were performed to plastically close deep and large burn wounds. We performed an arthrotomy in 31 patients. In all cases, arthrotomy was performed as a planned surgical intervention. Unfortunately we performed amputation in 8 patients. Results: In the postoperative period, drainage of the joint cavity through the opening and wound, the application of paraphene to the surrounding tissues of the joints, massage, physical therapy, treatment physical physiotherapy exercises, laser application made it possible to achieve satisfactory results. Conclusions: The described herein method of treatment of purulent arthritis of the lower extremities has improved treatment results, expanded survival rates, reduced probability of complications and disabilities.